Social Discrimination: Violence and Resistance of Female 19th Century in Jane Austen’s Persuasion - Rezki Amelia Anggraeni; Ken Widyatwati; M Suryadi (Universitas Sanata Dharma, 2025)
he 19th century in England, particularly during the Victorian era was defined by rigid social norms and power structures that placed women in subordinated roles. Within this context, women were expected to perform traditional duties as wives and mothers with limited access to education or employment. Persuasion by Jane Austen illustrates this reality through female characters, who experience cultural violence from social inequality. This study examined the form of cultural violence endured by the female characters in Persuasion, which reflects the social discrimination that pervaded 19th-century society. The study aims to explore in depth how the social norms and power structures of that era contributed to injustices faced by women. The researcher used a sociological literature approach to answer these questions and applied Johan Galtung’s theories of cultural violence. The data was collected by analysis of expressions and dialogues in Persuasion, which reveal various forms of injustice, prejudice, and sarcasm toward female characters. The findings indicated that the novel’s female characters represent 19th-century women who encountered cultural violence, a concept illuminated through Galtung’s perspective. Notably, some characters resisted the cultural violence they faced, while others adopted a more passive stance, reflecting diverse responses to oppression within a broader social context.